Methoxyflavone derivatives modulate the effect of TRAIL-induced apoptosis in human leukemic cell lines - Benjawan Wudtiwai (2018)
Background: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) induces apoptosis in various tumor cells, but does not affect normal cells or human leukemic cells, such as MOLT-4 and U937 cells, which are relatively resistant to TRAIL. Three flavonoids extracted from the rhizome of K. parviflora were 5,7-dimethoxyflavone (DMF), 5,7,4'-trimethoxyflavone (TMF) and 3,5,7,3',4'-pentamethoxyflavone (PMF), and synthetic flavonoids including 5-methoxyflavone (5-MF) and 2'-methoxyflavone (2"-MF) were chosen for testing in this study. The aims of this study were to examine whether the treatment of TRAIL-resistant leukemia MOLT-4 and U937 cells, with methoxyflavone derivatives could enhance the apoptotic response and to identify the mechanism involved. Methods. The cytotoxic effect of methoxyflavone (MF) derivatives in MOLT-4, U937 and peripheral blood mononuclear cells (PBMCs) was analyzed by the MTT assay. The induction of apoptosis and the reduction of mitochondrial transmembrane potential (m) after staining with annexin V FITC and propidium iodide (PI), and 3,3'-dihexyloxacarbocyanine iodide (DiOC 6), respectively, were performed using flow cytometry. ROS production was determined by staining with 2',7'-dichlorofluorescin diacetate and processed with a flow cytometer. DR4, DR5, cFLIP, Mcl-1, BAX and Bid expression were demonstrated by immunoblotting. Caspase-8 and -3 activities were determined by using IETD-AFC and DEVD-AFC substrates and the fluorescence intensity was measured. Results: All methoxyflavone derivatives were cytotoxic to MOLT-4, U937 cells and PBMCs, except DMF, TMF and PMF were not toxic to PBMCs. All MF derivatives induced human leukemic MOLT-4 cell apoptosis, but not in U937 cells. Percentage of MOLT-4 cells with (m) was increased when treated with DMF, TMF, PMF, 5-MF and 2'-MF in the presence of TRAIL. 5-MF and 2'-MF enhanced TRAIL-induced apoptosis through the up-regulation of both DRs and the down-regulation of cFLIP and Mcl-1. Bid was cleaved and BAX was up-regulated, followed by the activation of caspase-8 and -3. Oxidative stress was also increased. 2'-MF gave the same result compared with 5-MF but with a less effect. Conclusion: Methoxyflavone derivatives enhanced TRAIL-induced apoptosis in human leukemic MOLT-4 cells through the death receptors and mitochondrial pathways. © 2011 Wudtiwai et al; licensee BioMed Central Ltd.